2008
DOI: 10.1175/2007jas2337.1
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of a Northern Hemisphere Atmospheric Blocking Climatology

Abstract: A comprehensive climatology of Northern Hemisphere blocking is described based on a PV-wavebreaking index at the latitude of the climatological storm track and using the 40-yr ECMWF Re-Analysis (ERA-40) dataset. The general characterization of blocking regions is in agreement with most other studies, though more detail is provided here. In the annual average, blocking is most prevalent in the large region from the eastern Atlantic Ocean through Europe to central Asia with a secondary region in the central and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
142
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(162 citation statements)
references
References 52 publications
(59 reference statements)
18
142
1
1
Order By: Relevance
“…The described blocking was located between 50 • N-60 • N, the latitude where most blocking events occur. The mean duration of blocking events over Europe was found to be between 7.6-8 days (Tyrlis and Hoskins, 2008). Thus, the blocking event in May 2008 which lasted 12 days, was exceptionally persistent.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The described blocking was located between 50 • N-60 • N, the latitude where most blocking events occur. The mean duration of blocking events over Europe was found to be between 7.6-8 days (Tyrlis and Hoskins, 2008). Thus, the blocking event in May 2008 which lasted 12 days, was exceptionally persistent.…”
Section: Discussionmentioning
confidence: 93%
“…4). Several climatologies of blocking events have shown that the European Atlantic region, at the end of the Atlantic storm track, is the region with the highest frequency of blocking events followed by the eastern Pacific region (e.g., Barriopedro et al, 2006;Tyrlis and Hoskins, 2008). The annual cycle shows maximum frequencies in the cold season.…”
Section: Discussionmentioning
confidence: 99%
“…Circulation Type 3 is meanwhile completely opposite to others. This regime is often referred to as Scandinavian blocking and is characterized by a strong positive height anomaly over Northern Europe [50]. Scandinavian blocking occurs on average 24.5% of the time during winter [51] and plays an important role in the Euro-Atlantic weather regime along with NAO and Atlantic Ridge.…”
Section: Resultsmentioning
confidence: 99%
“…In the Atlantic-European sector blocking occurs more frequently over the North Atlantic in winter but more frequently over Europe in summer (e.g. Tyrlis and Hoskins 2008). Blocking is a major contributor to intraseasonal variability in the extratropics and can lead to seasonal climate anomalies over large parts of Europe (e.g.…”
Section: Atmospheric Blockingmentioning
confidence: 99%